The young social care workforce in Wales: A longitudinal analysis of transitions into social care work using linked workforce and education data - Huxley, Katy (International Journal of Population Data Science, 2026)
The social care workforce in the UK is under strain, with significant recruitment and retention issues. This is highlighted by the English governments new commission into social care reform, and reforms in Scotland and Wales (such as registration and pay commitments). It is crucial to understand the pathways into social care jobs, who is and who isn't moving into social care roles, as the ageing population creates ever greater strains on an already fragile workforce. Using the social care workforce register (official records on registration of social care workers) and records on learners educated (from schools to higher education), we undertake unique longitudinal analysis for Wales. Data linkage and analysis enables us to explore issues pertinent to the future of this important sector, asking: 1) Who are the learners moving into social care jobs in Wales? 2) To what extent are the personal characteristics of learners and their education pathways associated with working in social care? 3) Are certain personal characteristics or educational pathways associated with different types of social care jobs? Descriptive findings show, overall: A significant continued gender division in social care work An underrepresentation of 'top' attainers and 'low' attainers Limited associations with socio-economic status Vocational (work-related) education is the more common education pathway Regression analysis shows associations between personal characteristics and educational pathways vary for different social care jobs (such as home care compared to social work). These findings are important for future social care workforce planning and recruitment.